HUBUNGAN DUKUNGAN ORANG TUA DENGAN HASIL BELAJAR SISWA KELAS X PROGRAM KEAHLIAN TEKNIK GAMBAR BANGUNAN SMK NEGERI 1 PARIAMAN SEMESTER JULI-DESEMBER 2015 - 1169-1188 , Mahyu Hendri Susilo (CIVED, 2016)
ABSTRACT              This research aims to determine how relationship there or not family support with study result in Competence Program  Technic Drawing Building SMK Negeri 1 Pariaman. The variabel is relationship family support with study result in Competence Technic Drawing Building SMK Negeri 1 Pariaman. The population is student class X SMK Negeri 1 total 64 responden. The Sampel in this research using proporsional random sampling total 55 responden. The instrumen in this research using questionaire with 5 choice answer in skala likert. The total expression is 22 item. Technic analisis data consist from Normalitas Test, LinieritasTest and HipotesisTest. The result in this research indicate that there relationship between support family with study result in Technic Drawing Building beacuse rhitung>rtabel (0,471>0,224). Therefore more and more good supoort family so more and more study result too.Keyword: Family Support, Study Result